Perceived oral health status and its association with oral health-related quality of life of patients with rheumatoid arthritis - a pilot study - Lim, Ching Ching; Wan Majdiah Wan Mohamad,; Norkhafizah Saddki,; Wan Syamimee Wan Ghazali, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Rheumatoid arthritis (RA) is an autoimmune disease that affects not only the joints, but also other organ systems including the oral cavity. Studies have demonstrated an association between RA and oral disease, in particular periodontal disease. This cross-sectional study aimed to determine self-reported oral health problems among RA patients and its association with oral health-related quality of life. A total of 67 RA patients attending the Rheumatology Clinic, Hospital Universiti Sains Malaysia participated in this study. Self-administered questionnaires including the Malay version of Short Oral Health Impact Profile [S-OHIP(M)] questionnaire were used to obtain the variables of interests. Most patients perceived their oral health status as good or very good (70.2%) although some reported having at least one oral health problem (40.3%). Commonly reported oral health problems were cavitated tooth (16.4%), swollen gums (16.4%), bad breath (14.9%), and bleeding gums (13.4%). Some patients have lost all upper teeth (32.8%) and all lower teeth (28.4%). The median S-OHIP(M) score was 3.00 (IQR 7.00). With regard to prevalence of impact, item discomfort due to food getting stuck has the highest prevalence of 13.4%, followed by avoided eating certain foods (7.5%). No significant association was found between median S-OHIP(M) score and self-reported oral health problem among RA patients, but a significant association was found between median S-OHIP(M) score and perceived oral health status (P=0.013). In conclusion, oral health problems were common in RA patients, and the association between patients’ oral health perceptions and severity of impact from oral problems was apparent.